ESTIMASI KERUGIAN EKONOMI AKIBAT STATUS GIZI BURUK DAN BIAYA PENANGGULANGANNYA PADA BALITA DI BERBAGAI PROVINSI DI INDONESIA - Muhammad Aries; Drajat Martianto (Food and Nutrition Society of Indonesia, 2006)
The study was aimed to estimate GDP lost due to Protein Energy Malnutrition (PEM) among under five children at various provinces in Indonesia. It was a descriptive study used secondary data. Data analysis was conducted in Bogor, from January to March 2006. The data uses are prevalence of PEM among under five children in various provinces in 2003, Gross Regional Domestic Product (GRDP) of provinces in Indonesia by industrial origin 2000 - 2004, population by province, sex and age group 2003, composite Consumers Price Index (CPI) of 45 cities (2002 = 100). The study showed that the economic lost due to malnutrition (PEM) among under five children in Indonesia was ranged from 0.27% to 1.21% GDP.